A holistic reliability system approach of a water distribution network in Saudi Arabia - Laith Hadidi (IWA Publishing, 2021)
Saudi Arabia, with no perennial rivers, is considered to be an arid land where water losses in the water distribution network (WDN) supply increase the need for sea water desalination. This paper provides a reliability model to enhance the WDN for a water pumping station in Saudi Arabia. The paper utilizes the fault tree analysis (FTA) reliability tool to mitigate water supply stoppages. In the case under study, the pump station utilizes two groundwater aquifers in the eastern part of Saudi Arabia to meet the raw water demand through a water distribution network (28 km-long pipelines). Data has been gathered from the maintenance history to estimate the system reliability based on the loss of water by which each component of the system is assessed on its contribution to the overall system reliability and water supply. The findings revealed that system availability can be improved by adding a new pump in the booster station which further enhances the availability of the system to 99.99% and saves the WDN more than 740,974.60 gallons of water loss per year. It is hoped that the paper's recommendations will enhance reliability practices in similar water network stations. HIGHLIGHTS The reliability of a community raw water distribution system in Saudi Arabia is assessed.; A reliability tool based on fault tree analysis is utilized to mitigate water supply stoppage.; Real data are collected to estimate system reliability.; The water distribution system availability is analyzed and improved.;